Gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS): a new autosomal dominant syndrome. Issue 5 (3rd August 2011) - Worthley, D L; Phillips, K D; Wayte, N; Schrader, K A; Healey, S; Kaurah, P; Shulkes, A; Grimpen, F; Clouston, A; Moore, D; Cullen, D; Ormonde, D; et al.
Abstract : Objective: The purpose of this study was the clinical and pathological characterisation of a new autosomal dominant gastric polyposis syndrome, gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS). Methods: Case series were examined, documenting GAPPS in three families from Australia, the USA and Canada. The affected families were identified through referral to centralised clinical genetics centres. Results: The report identifies the clinical and pathological features of this syndrome, including the predominant dysplastic fundic gland polyp histology, the exclusive involvement of the gastric body and fundus, the apparent inverse association with current Helicobacter pylori infection and the autosomal dominant mode of inheritance. Conclusions: GAPPS is a unique gastric polyposis syndrome with a significant risk of gastric adenocarcinoma. It is characterised by the autosomal dominant transmission of fundic gland polyposis, including areas of dysplasia or intestinal-type gastric adenocarcinoma, restricted to the proximal stomach, and with no evidence of colorectal or duodenal polyposis or other heritable gastrointestinal cancer syndromes.